Kerala’s Ombudsman: A Mismatch of Mission and Capabilities - JOSHUA J. M. STARK (Governance: An International Journal of Policy, Administration, and Institutions, 2011)
India, like many developing nations, has adopted many accountability institutions. One of these is the ombudsman. Originally a Swedish inven- tion, ombudsman’s offices were adopted by many countries over the last 50 years. Recently, the South Indian state of Kerala has instituted an ombuds- man’s office. While it has had notable successes in resolving minor cases related to local government institutions, it is severely constrained by an unresponsive state government. In particular, the Kerala ombudsman requires independent investigative powers and an expansion of its office.